Copyright literacy of LIS students in Portugal - Terra, Ana Lúcia; Martins, Fernanda; Pinto, Manuela (Qualitative and Quantitative Methods in Libraries, 2020)
With the spread of Information and Communication Technologies, in general, and with the availability of digital communication networks and mobile devices, in a more specific approach, unauthorized consumption of content has become an integral part of the daily lives of the majority of social actors in their multiple uses of the internet. In this context, information professionals and Library and Information Science (LIS) students will have an essential role to play. As far as LIS students are concerned, it is important to know what knowledge they have about copyright laws and what kind of content and approach should be followed in the curriculums. For this purpose, a multinational study regarding copyright literacy skills among LIS students, called Copyright Literacy of LIS Students (CoLIS) was designed. In this paper, some Portuguese results of data collected are presented and analyzed. The paper shows the key findings on familiarity, knowledge, awareness, and opinions on copyright issues of LIS students. A comparison with the results from other countries using the same survey instrument is undertake